Design och konstruktion av åror till snipa : Tillämpning av Design For Six Sigma - Molin, Mattias; Larsson, Adam (Linnéuniversitetet, Institutionen för maskinteknik (MT), 2023)
The oar has historically played a significant role for Sweden as a lake andcostal dominated country. For many years small boats called “snipa” wereused to gather fish by people living along the coastlines or alongside lakes.Oars was then the only option for conveying the boat forward. In today’ssociety, oar-propelled boats don’t have the same importance for people toacquire food. However, there are still reasons for a continued use of oars inactivities such as private fishing, competitive rowing or outdoor pursuits.The consumer market today is largely focused on mass production ofproducts, which often results in a reduced availability of custom-made ones.Being able to “engineer to order” is sometimes preferable due to the fact thathigh-quality and robust designs are, in certain respects, essential.Linnaeus University is conducting a research project that has vitalized atraditional Sami hunting and fishing gig boat, designed to be conveyed byoars and requires specially adapted oars for two different types of waterconditions. Currently, private consumers have limited options, for productsthat is designed for this, on the market.The purpose of this work is to describe how the established and well-knownmethodology of Systems Engineering, more specific “Design For SixSigma” (DMADOV), can be used to design and construct oars for use in twodifferent water conditions.